Original articleDistribution of HBV genotypes in Poland - Świderska, Magdalena; Pawłowska, Małgorzata; Mazur, Włodzimierz; Tomasiewicz, Krzysztof; Simon, Krzysztof; Piekarska, Anna; Wawrzynowicz-Syczewska, Marta; Jaroszewicz, Jerzy; Rajewski, Paweł; Zasik, Ewelina; Murias-Bryłowska, Elżbieta; Pniewska, Anna; et al. (Clinical and Experimental Hepatology, 2015)
Aim of the study : To identify distribution of HBV genotypes in particular regions of Poland. Material and methods : The study included 270 treatment-naïve, HBV-infected individuals, enrolled in 7 centers of Poland. HBV genotyping was performed in 243 of them with the INNO-LiPA HBV Genotyping assay (Innogenetics). Results : Genotype A present in 2/3 patients was demonstrated as the most predominant in Poland. It was followed by D (20%), H (5%) and mixed A + D (5%). Remaining patients were infected with genotype F, mixed D + G, A + C or D + F. Analysis of distribution demonstrated regional differences, with a higher rate of genotype D prevalence (about 30%) in the eastern (Białystok and Lublin) and south-western (Wrocław) parts compared to other regions, where the prevalence rate was below 15%. The highest prevalence of genotype A (exceeding 80%) was observed in central Poland (Bydgoszcz, Łódź). Conclusions : The presented data reveal the current distribution of HBV genotypes across Poland, which is the first and the largest such epidemiological analysis.